HUMAN RESOURCES DEVELOPMENT EFFORTS IN FACING THE SOCIETY 5.0 ERA IN INDONESIA - Rizaldi Azhar (UNIVERSITAS PAKUAN, 2022)
The quality of human resources is important in reducing the unemployment rate, since Society 5.0 aims to make people able to enjoy life to the fullest by utilizing technological advances, which has an impact on increasing economic growth. This article aimed to examine the Efforts to Develop Human Resources in Facing the Era of Society 5.0 in Indonesia by improving educational quality as a way of preparing the millennial generation for the era of digital transformation. The research method employed in this article was a qualitative method with a literature review. According to the findings of the study, in order to create professional and competent human resources in the period of society 5.0, it is necessary to improve the quality of education, involve the millennial generation, and also collaborate with the government and the business sector. It is expected that through adjusting to the changes and advancements of the times, Indonesia's human resources will have superior knowledge and abilities in the field of information technology in the future. This is useful for improving human resource competitiveness at multiple levels, including locally, nationally, and worldwide.